2019
DOI: 10.17352/2455-5479.000058
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the practices of caesarean section in sub-Saharan Africa: A summary of the literature

Abstract: Introduction:Ensuring access to quality caesarean sections (CS) is a challenge for the next millennium and a sustainable development goal to reduce maternal and infant mortality. A CS involves risks and complications and should therefore be performed in an approved way and not used excessively. The WHO recommends that the CS rate should not exceed 10-15%. Approximately 99% of maternal deaths occur in developing countries where efforts to reduce maternal deaths are still low. This review of the literature aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…One study analysed the proportion of CS in SSA and showed an average CS rate of 19% [13], which is in line with the overall estimate described in the literature [14]. Another study on the analysis of CS practices in SSA described a CS rate of 2 to 52% [15]. This study showed that this rate varies depending on the population studied and on access to healthcare [15,16].…”
Section: Caesarean Frequencysupporting
confidence: 58%
See 4 more Smart Citations
“…One study analysed the proportion of CS in SSA and showed an average CS rate of 19% [13], which is in line with the overall estimate described in the literature [14]. Another study on the analysis of CS practices in SSA described a CS rate of 2 to 52% [15]. This study showed that this rate varies depending on the population studied and on access to healthcare [15,16].…”
Section: Caesarean Frequencysupporting
confidence: 58%
“…Intra transfusion, wound suppuration, septicaemia, peritonitis, parting of stitches, urogenital fi stulae and hypertensive disorders. One study described the same maternal risks associated with CS in SSA [15]. Maternal mortality was 0.1%, and 0.1% of patients were transferred.…”
Section: Maternal Risksmentioning
confidence: 95%
See 3 more Smart Citations